MPLS Network Optimization for VoIP Using DiffServ with Multiple ER-LSP - Al-Asri, Mahmoud Ahmed A.; Zahary, Ammar T. A.; Mohsen, Abdulqader M. (American Association for Science and Technology (AASCIT), 2015)
Many transport carriers have been built their networks based on MPLS technology as a converged network that able to carry different types of traffic such as VoIP, video, and Internet, therefore it is important to build reliable network which provides guaranteed bandwidth and it can support congestion management mechanism. This can be achieved through integrating MPLS and DiffServ technologies; the MPLS provides end to end connectivity with multiple paths, while DiffServ classifies traffic based on its type. In this research, VoIP traffic performance has been analyzed in different cases with and without DiffServ/MPLS. The analysis covers performance parameters such as efficiency, end-toend packet delay and voice jitter. The result shows that VoIP can be delivered on MPLS-DiffServ as a reliable service with guaranteed bandwidth, where applying Class of Service (CoS) at Label Edge Router (LER) with setting QoS buffer sizes to the best values.